Potential for biomonitoring metals and metalloids using fish condition and tissue analysis in an agricultural and coal mining region. (July 2018) - Chua, Evan M.; Flint, Nicole; Wilson, Scott P.; Vink, Sue
Abstract: Agricultural and mining activities contribute to metal inputs in freshwater ecosystems around the world, which can in turn bioaccumulate in biota such as fish. Monitoring of metals loads in biota thus provides insight into the concentrations of bioavailable metals within the environment. Little research has been conducted on the potential of Australian freshwater fish for biomonitoring metals. Within the Fitzroy Basin of Central Queensland, a major agricultural and coal mining region, three commonly-encountered fish taxa were analysed for tissue metal loads. Arsenic concentrations in Nematalosa erebi and Melanotaenia splendida splendida tissue were elevated (above Food Standards Australia and New Zealand (FSANZ) guidelines), with highest concentrations in N. erebi liver tissue (up to 5.14 μg/g). Lead concentrations were above the FSANZ guidelines in all three fish taxa analysed, with highest concentrations in Hypseleotrid full-body tissue (up to 5.99 μg/g). Selenium in M. s. splendida and N. erebi tissue was positively correlated with total selenium in water ( p  < 0.05; r  = 0.68 and 0.87 respectively). Environmental boron, selenium and nickel concentrations were positively correlated with N. erebi liver tissue metals. N. erebi hepatosomatic index was negatively correlated with dissolved arsenic, manganese, and total phosphorus (in water). The results highlight that M. s. splendida and N. erebi yield bioindicators which are responsive to environmental metals, and thus have potential for use in biomonitoring metals. The two species are also widespread along the east coast of Australia, there is thus a strong potential for applying the results to other regions within Australia. Graphical abstract: Image 1 Highlights: Tissue As and Pb concentrations were elevated in three species. Positive correlation between environmental and tissue Se and Ni in two species. Two Nematalosa erebi bioindicators were negatively correlated with environmental Ni. N. erebi and Melanotaenia splendida splendida have potential as metal biomonitors.